The Open Educational Resources (OER) movement: Free learning for all students - McGreal, R.; Sampson, Demetrios; Chen, N.; Kinshuk; Krishnan, M.; Huang, R. (2012)
In recent years, the term Open Educational Resources (OER) has emerged, aiming to promote open access to digital educational resources that are available online for everyone at a global level. This panel presents views from different countries on the development of open educational resource initiatives. © 2012 IEEE.